Pricing (Almost) Any Used Goods: A First Step Towards a Theoretical Framework - CIANNI, Victor (Journal of Advanced Studies in Finance; Vol 12 No 1 (2021): JASF Volume XII Issue 1(23) Summer 2021, 2021)
From the latest technological gadget to the multi-century collectible item, millions of used goods are exchanged on marketplaces every day. Yet, there have been very few attempts to propose a pricing theory that could help buyers and sellers set a price at any point in time. In this paper, we build a robust framework and introduce a cohort-specific model to explain how the price of used goods evolves over time. Despite its simplicity, we believe that this model could be applied to an extensive range of used goods.